Self-viewing is associated with negative affect rather than reward in highly narcissistic men: an fMRI study - Emanuel Jauk (Nature Portfolio, 2017)
Abstract Subclinical narcissism is a personality trait with two faces: According to social-cognitive theories it is associated with grandiosity and feelings of superiority, whereas psychodynamic theories emphasize vulnerable aspects like fluctuating self-esteem and emotional conflicts. The psychodynamic view, however, is commonly not supported by self-report studies on subclinical narcissism. Personality neuroscience might help to better understand the phenomenon of narcissism beyond the limits of self-report research. While social-cognitive theory would predict that self-relevant processing should be accompanied by brain activity in reward-related areas in narcissistic individuals, psychodynamic theory would suggest that it should be accompanied by activation in regions pointing to negative affect or emotional conflict. In this study, extreme groups of high and low narcissistic individuals performed a visual self-recognition paradigm during fMRI. Viewing one’s own face (as compared to faces of friends and strangers) was accompanied by greater activation of the dorsal and ventral anterior cingulate cortex (ACC) in highly narcissistic men. These results suggest that highly narcissistic men experience greater negative affect or emotional conflict during self-relevant processing and point to vulnerable aspects of subclinical narcissism that might not be apparent in self-report research.